Literatura de tradição oral indígena: instrumento dedático-pedagógico e de valorização dos conhecimentos dos povos indígenas. - Santos, Shayana da Silva. (Universidade Federal do Tocantins, 2021)
The objective of this study that investigated indigenous literature of oral tradition is to understand the relationships between literature of oral tradition, memory, and indigenous identity and how they are articulated in a didactic-pedagogical instrument and of valuing the knowledge of indigenous peoples. For that, we verified, from the studied references, the relations between literature of indigenous oral tradition and academic literature; we verify possible connections between memory and identity in indigenous literature of oral tradition; and we point out possibilities of using indigenous oral literature as a didactic-pedagogical tool in the indigenous school. This is a bibliographic study that establishes approximations with Post-colonialism and with Decolonial Thought as critical theories of reflection, and that used scientific publications in journals, dissertations, and theses as a source for a review about the knowledge already produced on the theme studied. The data show that some factors, such as the Indian and Indian writings, directly influenced the constitution of indigenous literature in Brazil. Memory and identity in indigenous literature of oral tradition are always transformed, updated and enriched according to new knowledge and values added to the experiences of indigenous peoples. We found that the literary and pedagogical richness of indigenous narratives is fueled by difference and that it is a multimodal literary writing with its own characteristics. However, teachers are still unaware of indigenous authors and their works and/or judge by western canonical criteria, which can contribute to a prejudiced and stereotyped pedagogical practice in the approach to indigenous literature at school.